2022
DOI: 10.3389/fpls.2022.806765
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of KNOX Transcription Factors and Expression Pattern of Dwarf-Related KNOX Genes in Pear

Abstract: KNOTTED1-like homeobox (KNOX) transcription factors (TFs) belonging to the homeobox TF family play important roles in plant growth, development, and responses to abiotic and biotic stress. However, little information is available on KNOX TF in pear (Pyrus). In this study, 19 PbKNOXs TFs were re-identified in pear (Pyrus bretschneideri Rehd.). Phylogenetic analysis revealed that the TFs were clustered into three groups with 10 conserved motifs, some of which were group- or subgroup-specific, implying that they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…A later study found that the silencing of GhKNOX10 and GhKNOX14 in cotton reduced the tolerance of seedlings to salt stress, while the silencing of GhKNOX2 enhanced the salt tolerance of cotton seedlings (Zhang et al, 2021b). Members of the pear KNOX subfamily can respond to drought stress treatment, specifically, the expression of PbKNOX7/13 is increased under drought stress, while the expression of PbKNOX5/16 is inhibited under drought stress (Liu et al, 2022). In this study, the promoter analysis of TALE genes of P. mume revealed a variety of abiotic stress elements, including low temperature, drought, hypoxia induction, and trauma response.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A later study found that the silencing of GhKNOX10 and GhKNOX14 in cotton reduced the tolerance of seedlings to salt stress, while the silencing of GhKNOX2 enhanced the salt tolerance of cotton seedlings (Zhang et al, 2021b). Members of the pear KNOX subfamily can respond to drought stress treatment, specifically, the expression of PbKNOX7/13 is increased under drought stress, while the expression of PbKNOX5/16 is inhibited under drought stress (Liu et al, 2022). In this study, the promoter analysis of TALE genes of P. mume revealed a variety of abiotic stress elements, including low temperature, drought, hypoxia induction, and trauma response.…”
Section: Discussionmentioning
confidence: 99%
“…The promoters of TALE gene family members in soybean contained cis-elements that responded to various stresses, and the expression level of GmTALE genes could change in response to salt stress and drought stress (Wang et al, 2021). Overexpression of the KNOX-like gene TaKNOX11-A of Triticum aestivum in A. thaliana can increase the content of proline and reduce the content of malondialdehyde, thereby enhancing the salt tolerance and drought resistance of the plant (Han et al, 2022). Cotton BELL-like gene GhBLH5-A05 plays an important role in combating drought stress.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Genes with similar amino acid sequences usually have similar functions, and vice versa ( Liu et al, 2022 ). Eight TTG1 proteins from different plants were found to be 78.2%–99.12% homologous, indicating that the functions of TTG1s are conserved in different species.…”
Section: Discussionmentioning
confidence: 99%